Growth analysis of the bitter gourd Momordica charantia L. crop in nursery phase - Barraza A., Fernando Vicente; B., Orlando Benavides; Tamayo A., Yonger (Revista de Ciencias Agrícolas, 2015)
An experimental field research study was conducted with vegetable crops at the University of Cordoba, Colombia, with the objective of analize the growth of bitter gourd seedlings Momordica charantia L obtained from seeds under pre-planting treatments, given the presence of a very thick seed coat that causes growth delay. A completely randomi zed design was used. Af ter ext ract ion f rom t he plant, t he seeds were subjected to the following treatments: T1 (control), T2 (seeds rinsed with ambient temperature water (TA)), and T3 (seeds submerged in ambient temperature water during 24 hours). The study variables were leaf area (AF), dry leaf matter (MSH), total dry matter (MST), absolute growth rate (TAC), relative growth rate (TRC), net assimilation rate (TAN), specific leaf area (AFE), leaf area index (IAF), leaf area ratio (RAF), and leaf weight ratio (RPF). A sigmoidal trajectory was found, which adjusted to the logistic model in AF, MSH, and MST. In regards to AF and MST, treatment 3 exceeded the other treatments at days 15, 21, and 24 after planting (dds). Regarding TAC, AFE, RAF, and RPF, a normal distribution graph was observed. A higher TAC was obtained for T3 at day 16 (0.023 g∙day-1). For TAN and TRC, a declining behavior was observed throughout time. The IAF was highest for T3 during the entire nursery phase.